Comparison of histopathologists' workloads in two pathology departments in Croatia - Jakić-Razumović, J; Tomić, S; Karaman, I (Croatian medical journal, 2001)
To calculate workloads of Departments of Pathology and staff histopathologists at two Croatian University Hospitals by means of the Suvarna and Kay's Kim Unit (KU) activity index. The total number of specimens and KU activity/year were calculated to compare staff pathologists' workload in two Pathology Departments, one at Split and the other at Zagreb University Hospital. The individual specimen types were assigned a difficulty score on a scale of 1-5 units (KUs), depending on the time needed for specimen dissection and macroscopic description, number of sections and stains required, and time spent on microscopy of an "average case". KU activity was calculated for all pathologists individually in terms of histology (1-5 KUs), autopsy (10 KUs), supervision of residents, and outside consultations (2 KUs). According to calculated Kim Unit activity index, pathologists' workload in two investigated pathology departments was not equally spread. In the Split Department of Pathology the distribution of workload was more uniform than in the Zagreb Department of Pathology. The average workload of both institutions was 4,562 KUs. KU activity index is a very useful method for assessing average pathologists' workload. It may be also used in hospital administration for predicting changes in service and number of working pathologists.